Previous Gestational Diabetes Increases Atherogenic Dyslipidemia in Subsequent Pregnancy and Postpartum. Issue 4 (6th May 2018) - Prados, Montserrat; Flores‐Le Roux, Juana A.; Benaiges, David; Llauradó, Gemma; Chillarón, Juan J.; Paya, Antoni; Pedro‐Botet, Juan
Abstract: In a cohort of women with previous gestational diabetes mellitus (GDM), we aimed to ascertain whether women with abnormal glucose tolerance 1‐year postdelivery had a more atherogenic lipid profile during and after pregnancy than those with normal glucose tolerance. A prospective cohort study with longitudinal design between January 2004 and March 2016 was conducted. Three hundred and six (56.8%) of 537 women diagnosed with GDM during the studied period attended a control visit during the first year after delivery. Of these, 112 (36.6%) had prediabetes and 16 (5.2%) had type 2 diabetes mellitus. No significant differences during pregnancy were found in total, low‐density lipoprotein, high‐density lipoprotein (HDL) cholesterol, and triacylglycerol (TAG) concentrations among the three groups. Only HDL cholesterol and TAG levels differed significantly among groups at 2 and 12 months after delivery. Logistic regression analysis revealed pregnancy HDL and glucose metabolism status to be associated with the HDL cholesterol concentration 1‐year postdelivery. Furthermore, the only independent factor associated with TAG levels 1 year after delivery was the gestational TAG concentration. In summary, an overweight multiethnic group of women with prior GDM presented a high incidence of postpartum dysglycemia (41.8%). HDL‐cholesterol and TAG levels, both components of the metabolic syndrome, differed significantly among the three study groups in the glucose‐metabolism status at 2 and 12 months after delivery. Women with previous GDM must be followed up in the postpartum period for early detection and management of lipid and glucose disorders.